2016
DOI: 10.3171/2015.4.spine141004
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between cervical spine sagittal alignment and clinical outcome after cervical laminoplasty for ossification of the posterior longitudinal ligament

Abstract: OBJECT The goal of this study was to determine the relationship between cervical spine sagittal alignment and clinical outcomes after cervical laminoplasty in patients with ossification of the posterior longitudinal ligament (OPLL). METHODS Fifty consecutive patients who underwent a cervical laminoplasty for OPLL between January 2012 and January 2013 and who were followed up for at least 1 year were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 25 publications
3
49
2
Order By: Relevance
“…This goes conform with other studies [22]. Due to different reasons (cage subsidence, loss of lordosis due to surgical technique) all of the delta groups ended up at similar mean one-year Cobb angles, and may be why there does not appear to be a difference comparing clinical parameter.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This goes conform with other studies [22]. Due to different reasons (cage subsidence, loss of lordosis due to surgical technique) all of the delta groups ended up at similar mean one-year Cobb angles, and may be why there does not appear to be a difference comparing clinical parameter.…”
Section: Discussionsupporting
confidence: 90%
“…Nonetheless, numerous studies also exist that do not see any clear correlation between clinical outcome and cervical lordosis [2, 22, 23]. Furthermore, patients with a severe kyphosis can often not be corrected into a physiological lordosis but still profit substantially from surgery [24].…”
Section: Introductionmentioning
confidence: 99%
“…For patients with OPLL, Iwasaki et al [17] observed deterioration of cervical alignment after laminoplasty, but there was no significant difference in surgery-related outcomes between patients with lordotic and those with kyphotic alignment. Lee et al [18] reported that, although laminoplasty increased the probability of kyphosis, the cervical sagittal alignment and clinical outcome were not clearly related in patients with OPLL. In this study, we attributed the lower JOA recovery rate of the NEP group to their severe canal occupying ratio and poor preoperative neurological function.…”
Section: Discussionmentioning
confidence: 99%
“…However, postoperative cervical kyphosis occurs at 5% to 30% after ELAP, even if preoperative CL is maintained [5][6][7] , and there are some studies investigating the preoperative factors related to postoperative cervical kyphosis after ELAP [5][6][7][8] . Lee et al reported that in 35 of 50 cases (70%), CL decreased after ELAP 9) . In cases with OPLL, a postoperative kyphotic deformity would be a particularly critical complication because laminoplasty does not decompress the The proportion of men was higher in OPLL than that of CSM.…”
Section: Introductionmentioning
confidence: 97%